The effect of cord clamping time on cord blood gas in term newborn babies delivered by cesarean section - Sema Tanrıverdi; Burak Pelit; İbrahim Tekinli (Perinatal Medicine Foundation, 2023)
Objective: Umbilical cord clamping time is a situation that should be planned before delivery. It is recommended that the umbilical cord be clamped for at least 30-60 seconds after birth in healthy preterm and term newborns. There are few studies investigating the effect of umbilical cord clamping time on cord blood gas. If the umbilical cord is clamped before 30 seconds after birth, it is considered early clamping, and if it is clamped after 30 seconds, it is considered late clamping. In this study, we aimed to compare the early or late clamping time of the umbilical cord with the acid-base parameters and lactate values of babies. Methods: A total of 217 term newborn infants who were delivered by cesarean section between December 2020 and December 2021 in our hospital, whose umbilical cord clamping times were recorded and who had cord blood samples, were included in our study retrospectively. pH, pCO2, pO2, HCO3, BE, lactate, Hb and bilirubin values in cord blood gas samples were compared between the two groups. Results: Two hundred seventeen term newborn babies were included in the study. Cord clamping time of infants was delayed in 125 (57.6%) and early in 92 (42.4%) infants. The mean pH in cord blood gas was 7.37±0.07 (7.16-7.57), pCO2 was 39.73 ±8.97 (20.3-65.4) mmHg, pO2 was 53.42±41.95 (14.8-198) mmHg, BE was -2.18±2.90 (-11.9-13.6) mmol/L, lactate was 2.12±0.88 (0.50-5.90) mmol/L, Hb was 14.57± 2.54 (10-23.7) g/dl, and bilirubin was 1.71±1.33 (0-3.7) mg/dl. Conclusion: There was no significant relationship between early and late clamping of the umbilical cord and acid-base parameters, and hemoglobin values in cord blood gas in term newborn babies delivered by cesarean section.